Efficacy of anti-interleukin-6 receptor antibody (tocilizumab) in colombian patients with takayasu’s arteritis (2013)
Background Takayasu’s arteritis (TA) is a chronic vasculitis that involves aorta and its main branches, where interleukin-6 (IL-6) seems to play a pathogenic role (1,2). The effect in four patients treated with the anti-IL-6 receptor (IL-6R) antibody Tocilizumab was evaluated. Objectives to describe the effect of Tocilizumab in patients of Takayasu’s arteritis. Methods We reviewed the clinical records of 4 patients with TA diagnosed according to current criteria, treated between 2010 and 2011 in a tertiary center in Cali, Colombia. Four patients with a refractory disease to multiple treatments, was began treatment with Tocilizumab at a dose of 8 mg/kg every month in association with metothrexate and/or steroids. Two patients were treated previously with infliximab (IFX) without control of disease. This cases were reported previously (3). Results The cases summaries are as follows: Case 1. A 30 year-old woman with a diagnosis of TA since 2003 presented panaortitis, with involvement of supra-aortic,